Effect of Hygrothermal History on Water and Mechanical Properties of Glass/Vinylester Composites - de la Osa, Orlando (2006)
The effects of hygrothermal aging on the mechanical and viscoelastic properties of vinylester (VE)/unidirectional glass-fiber composites are reported. The studies are done by means of a dynamometer (INSTRON) and a dynamic mechanical thermal analyzer (Perkin Elmer). The studies are carried out at three different temperatures: 20, 40, and 60 C. The adhesion between the fibers and matrix is studied by scanning electron microscopy (SEM) microphotographs. Flexural strength, flexural modulus, storage modulus in the glass state (Tg - 50 K), in rubber state (Tg + 50 K), and the glass transition temperatures are also investigated. These parameters are determined in the case of the matrix and composites materials, for the initial and final states. The diffusion coefficients are calculated by using the simplest Fick's equation.